Bancassurance Business Strategy in Life Insurance: a Case Study One of Joint Venture Company in Indonesia - Abiyyu, Ikhwan; Najib, Mukhamad; Asmara, Alla (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
This research will conduct bancassurance business strategy for one of life insurance company. Bancassurance business in Indonesia is wide open and needed the right strategy for every company. Life insurance companies in the bancassurance business hold an important roles as a party that providing the product for bank customers. The mapping is carried out for the current business conditions run by the company using BMC tool and will be deepened with a SWOT analysis for each component in BMC. To present a new market, the company need to apply a new strategy that has never been carried out by competitors, with the perspective of BOS, a write off-reduce-increase-create scheme will be implemented to produce BMC alternatives. The result showed three strategic issues for the company, there are product development by collaborating with general incurance, customer segmentation development especially for High Net Worth customers also offering product with foreign currency, and digital competency strengthening in selling and internal process. These three strategies can be used as extra ammunition for the life insurance companies to compete in the bancassurance business.